PMU-based state estimator for micro-grids - Soh, Wee Cheng. (2010)
In order to correctly determine the state of the micro-grid network, a state estimator plays an important role. This project aims to formulate Weighted Least Square (WLS) state estimation using Phasor Measurement Units (PMU). First, relevant work will be reviewed and compared. Then, the algorithm for state estimation and bad data processing will be developed. Results of the state estimation and bad data identification and elimination are also presented. Finally, how LabView is being used as real-time data acquisition and processing will also be explained.